STAGES OF DEVELOPMENT OF DRY ART - Ortiqova, Ozoda; Nazirova, Nafisa (Физико-технологического образование, 2021)
In this article, the authors provide extensive information on the history and developmental stages of the art of American quilting. At the same time, important ideas about the importance of quilting art were noted